KEANEKARAGAMAN JENIS IKAN DI SUNGAI ENIM KABUPATEN MUARAENIM PROVINSI SUMATERA SELATAN |Fish Diversity in River Enim, Muara Enim Regency, South Sumatera Province] - Afreni Hamidah (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2004)
Study mi fish diversity was conducted from September 2002 until February 2003. The aim Of study is to determine fish species living in River Enim. Survey method and purposive random sampling were used. Fish sampling using some equipments, such as cast net, drift gillnet. hook and line, and bamboo trap. The result indicated that there were 28 species in 11 families, and four orders. Family Cyprmidae has the most numerous fish (14 species), followed by Cobitidae (4 species) and Balitoridae (2 species). The other families have one species only.